2020
DOI: 10.1158/2326-6066.cir-19-0877
|View full text |Cite
|
Sign up to set email alerts
|

CD226hiCD8+ T Cells Are a Prerequisite for Anti-TIGIT Immunotherapy

Abstract: Clinical trials are evaluating the efficacy of anti-TIGIT for use as single-agent therapy or in combination with PD-1/PD-L1 blockade. How and whether a TIGIT blockade will synergize with immunotherapies is not clear. Here we show that CD226 lo CD8 + T cells accumulate at the tumor site and have an exhausted phenotype with impaired functionality.In contrast, CD226 hi CD8 + tumor-infiltrating T cells possess greater self-renewal capacity and responsiveness. Anti-TIGIT treatment selectively affects CD226 hi CD8 +… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 51 publications
3
63
0
Order By: Relevance
“…For example, our data also demonstrated that αTIGIT resulted in decreased DNAM expression on CD8 + T cells, which itself could lead to increase mortality in memory mice with sepsis. This possibility is consistent with a recent study that showed CD226 hi CD8 + T cells are required for the efficacy of anti-TIGIT immunotherapy in a tumor model (31). In our study, although αTIGIT affected the expression of this costimulatory receptor, it had no effect on the expression of numerous coinhibitory molecules, including PD-1, 2B4, and TIM-3 on CD44 hi or CD44 lo T cells either in previously naive or memory mice with sepsis.…”
Section: Jcisupporting
confidence: 93%
“…For example, our data also demonstrated that αTIGIT resulted in decreased DNAM expression on CD8 + T cells, which itself could lead to increase mortality in memory mice with sepsis. This possibility is consistent with a recent study that showed CD226 hi CD8 + T cells are required for the efficacy of anti-TIGIT immunotherapy in a tumor model (31). In our study, although αTIGIT affected the expression of this costimulatory receptor, it had no effect on the expression of numerous coinhibitory molecules, including PD-1, 2B4, and TIM-3 on CD44 hi or CD44 lo T cells either in previously naive or memory mice with sepsis.…”
Section: Jcisupporting
confidence: 93%
“…In addition, a recent study showed that treatment with an agonistic antibody targeting glucocorticoid-induced tumor necrosis factor receptor-related protein (GITR) in combination with a PD-1-blocking antibody generated memory CD8 T cells with high proliferative capacity, resulting in a synergistic regression of tumors 72 . Notably, the authors showed that the effect was predominantly dependent on CD226 signaling, which is enhanced by both GITR and PD-1 blockade; this finding is also in line with our results and those of others highlighting the role of CD226 in TIGIT blockade 73 . Collectively, these reports alongside our data strongly suggest that one of the principal mechanisms of actions of TIGIT blockade can be the modulation of the differentiation and memory status of tumor-reactive T cells.…”
Section: Discussionsupporting
confidence: 93%
“…This was supported by several studies showing that the co-stimulatory effects driven by targeting the TIGIT/PVR interaction are dependent on the engagement of DNAM-1 by PVR (27,29). A recent study suggested that the infiltration of CD8 + DNAM-1 high T cells into TME may predict the efficacy of TIGIT blockade, as the presence of these cells is essential for the anti-TIGIT immunomodulatory activity (30). Additional complexity arises from the direct interruption of DNAM-1 homodimerization by TIGIT which results in its impaired functionality (29).…”
Section: Dnam-1: the Central Co-stimulatory Molecule In An Interactinmentioning
confidence: 77%
“…Moreover, unlike CTLA-4, TIGIT has been shown to directly interact with DNAM-1, reducing the ability of DNAM-1 to homodimerize and enhance immune activation (27,29,42). Recently, it was demonstrated that the TIGIT/PVR interaction induces de-phosphorylation of DNAM-1 at tyrosine 322 and interferes with its co-stimulatory responses on T cell (43). In addition to counteracting the stimulatory function of DNAM-1 via direct binding and competition for their common PVR ligand, TIGIT can directly inhibit T and NK cell effector function by signaling through an ITIM domain (8,44).…”
Section: Tigit Blockade -A Promising New Clinical Modality For Treatimentioning
confidence: 99%